Impact of control behaviour on unacceptable variation in acrylamide in French fries. - Sanny, M.; Luning, Pieternel A.; Marcelis, Willem J.; Selamat, Jinap; Van Boekel, Martinus A. J. S. (Elsevier, 2010)
Various studies have identified high concentrations of acrylamide in French fries and they emphasised that there is much uncertainty about actual concentrations in French fries upon consumption. The aim of this study was to get insight in technological as well as people related factors that contribute to variable and high acrylamide concentrations in French fries prepared under typical food service establishment circumstances. The literature study indicated that glucose and fructose, and actual frying conditions (time-temperature) are the dominant technological factors in acrylamide formation and inadequate control of these factors can result in variable and high concentrations in French fries upon consumption. Analysis of the common control situation in FSE revealed that control decisions on resources by management (i.e. appropriate suppliers, specified raw materials, adequate frying equipment, competent personnel) can be effective in lowering acrylamide formation, but are restricted in practice. However, even under appropriate technological (advanced equipment, low reducing sugars in raw materials) and managerial conditions (competent people, appropriate procedures, etc), it is expected that daily control of food handlers (at receipt and during frying) may be still a major factor contributing to variable concentrations in acrylamide.